Perception of social exclusion by digital media in postgraduate students: Analysis of social exclusion and types of digital divide in an online postgraduate course - Sosa Mendoza, Raúl; Flores Aguilera, Glenda Mirtala; Torres Cosío, Verónica (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
Today, having digital skills and access to technological devices is of utmost importance to continue learning. This study analyzes the perception of digital exclusion by students enrolled in an online graduate program. The Results show that students have access to digital devices and Internet, and that the perception of exclusion is mainly due to the lack of digital skills. Subjects of this study who do not feel excluded, consider the existence of a school gap, due to their greater use and knowledge of digital tools with regards to the application made by the institution.